Pro-environmentalism behavior, organizational pressure, sustainable information technology initiatives and financial performance of Malaysian service firms - Jaafar, Noor Ismawati; Ainin, Sulaiman; Ali, Suhana Mohezar (2018)
Many firms are beginning to use sustainable Information Technology (IT) initiatives in their daily operations. The usage is generally associated with several factors, among them pro- environmentalism behavior and organizational pressure. Furthermore, the usage of sustainable IT initiatives has been considered to have influenced the financial performance of firms. Hence, this paper seeks to examine the factors associated with sustainable IT usage and their impact on the financial performance of threehundred and twenty-eight Malaysian services firms. Structural equation modeling was used and it was found that proenvironmentalism behavior and organizational pressure are associated with the usage of sustainable IT initiatives by organizations and that there is a correlation between pro-environmentalism behavior and organizational pressure. In addition, there is also sufficient empirical evidence to support a relationship between sustainable IT initiatives usage and financial performance.